2022
DOI: 10.1177/11786388221101829
|View full text |Cite
|
Sign up to set email alerts
|

Evenness of Dietary Protein Intake Is Positively Associated with Lean Mass and Strength in Healthy Women

Abstract: Background: Evenness of protein intake is associated with increased lean mass, but its relationship with muscle strength and performance is uncertain. Objectives: We determined the association of evenness of protein intake with lean mass, muscle strength and endurance, and functional ability. Design: This was a cross-sectional study. Setting: Data were collected at a research university in the upper midwestern United States. Participants: One hundred ninety-two healthy women, aged 18 to 79 years, mean ± SEM 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We demonstrated a positive association between the frequency of meals of ≥0⋅4 g/kg BW and BMI-muscle strength in female older adults. Two recent studies also investigated associations between muscle strength and consuming at least 0⋅4 g/kg BW in older adults ( 51 , 54 ) . While both studies did not adjust muscle strength for BMI, Johnson et al did account for BMI in their multiple regression analyses and found an association between absolute muscle strength and consuming at least 0⋅4 g/kg BW in females older adults ( 54 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated a positive association between the frequency of meals of ≥0⋅4 g/kg BW and BMI-muscle strength in female older adults. Two recent studies also investigated associations between muscle strength and consuming at least 0⋅4 g/kg BW in older adults ( 51 , 54 ) . While both studies did not adjust muscle strength for BMI, Johnson et al did account for BMI in their multiple regression analyses and found an association between absolute muscle strength and consuming at least 0⋅4 g/kg BW in females older adults ( 54 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies also investigated associations between muscle strength and consuming at least 0⋅4 g/kg BW in older adults ( 51 , 54 ) . While both studies did not adjust muscle strength for BMI, Johnson et al did account for BMI in their multiple regression analyses and found an association between absolute muscle strength and consuming at least 0⋅4 g/kg BW in females older adults ( 54 ) . Gingrich et al , on the other hand, found no relationship between the number of meals providing 0⋅4 g/kg BW and muscle strength ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…According to the recommendations by the European Society for Clinical Nutrition and Metabolism (ESPEN), individuals suffering from an acute of chronic disease should increase their protein intake by 50-90% (~1.2-1.5 g/kg/bm per day) above the RDA and maintain an energy intake of 25-30 kcal/kg/day [169]. For older adults, a phased protein intake of 25-30 g of protein three times a day is recommended to optimise the rates of muscle protein synthesis (MPS) [17,[176][177][178]. This extra intake is needed because older individuals tend to be less sensitive to anabolic stimuli such as protein and prone to 'anabolic resistance' [178,179].…”
Section: Optimising Nutritional Interventions For Sarcopenia and Cvd/...mentioning
confidence: 99%
“…In ADF or TWF, the modified fasting days involving intakes of ~500–600 kcal are best served by predominating that allotment with high-quality protein sources. Some evidence indicates that spreading protein consumption throughout the day positively influences muscle protein synthesis (MPS) [ 69 , 70 ] and lean mass [ 71 , 72 ]; hence, IF strategies that employ an overly narrow feeding window may be suboptimal in this regard. For example, Tinsley et al [ 35 ] found that a 4/20 feeding/fasting distribution attenuated gains in lean mass in young men undertaking an eight-week resistance training program.…”
Section: Concluding Perspectives and Practical Applicationsmentioning
confidence: 99%